The relevancy of controlled nanocrystallization on rifampicin characteristics and cytotoxicity - Mohyeldin SM (Dove Medical Press, 2016)
Salma M Mohyeldin, Mohammed M Mehanna, Nazik A Elgindy Department of Industrial Pharmacy, Faculty of Pharmacy, Alexandria University, Alexandria, Egypt Purpose: This article investigated the influence of novel rifampicin nanosuspension (RIF NS) for enhancing drug delivery properties. Methods: RIF NS was fabricated using the antisolvent precipitation technique. The impact of solvent type and flow rate, stabilizer type and concentration, and stirring time and apparatus together with the solvent–antisolvent volume ratio on its controlled nanocrystallization has been evaluated. NSs were characterized by transmission electron microscopy, particle size and zeta potential analysis, solubility, and dissolution profiles. The compatibility between RIF and the stabilizer was investigated via Fourier transform infrared spectroscopy and the differential scanning calorimetry techniques. The shelf-life stability of the RIF NS was assessed within a period of 3 months at different storage temperatures. Cell cytotoxicity was evaluated using 3(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay on lung epithelial cells. Results: Polyvinyl alcohol at 0.4% w/v, 1:15 methanol to deionized water volume ratio and 30-minutes sonication were the optimal parameters for RIF NS preparation. Nanocrystals were obtained with a nanometeric particle size (101 nm) and a negative zeta potential (-26 mV). NS exhibited a 50-fold enhancement in RIF solubility and 97% of RIF was dissolved after 10 minutes. The RIF NS was stable at 4±0.5°C with no significant change in particle size or zeta potential. The MTT cytotoxicity assay of RIF NS demonstrated a good safety profile and reduction in cell cytotoxicity with half maximal inhibitory concentration values of 0.5 and 0.8 mg/mL for free RIF and RIF NS, respectively. Conclusion: A novel RIF NS could be followed as an approach for enhancing RIF physicochemical characteristics with a prominence of a safer and better drug delivery. Keywords: controlled nanocrystallization, cytotoxicity, nanosuspension, polyvinyl alcohol, rifampicin